2020
DOI: 10.3233/bmr-181371
|View full text |Cite
|
Sign up to set email alerts
|

Global Postural Re-education in non-specific neck and low back pain treatment: A pilot study

Abstract: BACKGROUND: Spinal pain is an important public health issue that brings biopsychosocial problems. Global Postural Re-education (GPR) is one of its treatments. OBJECTIVE: Evaluate the effects of GPR on pain, flexibility, and posture of individuals with non-specific low back pain and/or neck pain for more than six weeks. METHODS: The study enrolled 18 individuals, which were randomized into two groups: GPR group (GPRG; n= 09), submitted to 10 sessions of GPR and control group (CG; n= 09), not submitted to any te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Additionally, although there is little previous evidence, results from previous studies with GPR have shown effects not only on symptom improvement, such as pain and functionality [55,56], but have also had effects on patient body awareness and proprioception associated with breathing and joint decompression [68,75,76]. Thus, in our study we anticipated that GPR would improve postural stability.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Additionally, although there is little previous evidence, results from previous studies with GPR have shown effects not only on symptom improvement, such as pain and functionality [55,56], but have also had effects on patient body awareness and proprioception associated with breathing and joint decompression [68,75,76]. Thus, in our study we anticipated that GPR would improve postural stability.…”
Section: Introductionmentioning
confidence: 84%
“…Global postural reeducation (GPR) is a conservative treatment that we can consider as a global postural exercise method, and widely used in physical therapy clinical practice in many countries [55,56]. Some studies support the clinical effectiveness of GPR in treating patients with different musculoskeletal disorders and impairments [57][58][59][60][61][62][63], including cranio-cervico-mandibular complex [64][65][66][67][68][69][70][71][72]. The main aims of GPR are to reduce postural impairments and regain muscle symmetry and adequate posture through global active muscular stretching postures and joint decompressions, with breath control, motor control, contractions of antagonist muscles, and sensory integration exercises conducted by manual contacts in order to provide proprioceptive information to the patient [61,[73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neck pain may occur as a result of imbalances in the biomechanics of the neck and abnormalities in the entire alignment throughout the body. Recent studies have shown that global posture re-education is an effective treatment for chronic pain, including neck and low back pain [12][13][14] . Meanwhile, some studies have provided evidence that ergonomic assistive devices are useful for correcting poor posture [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Estudios previos con RPG han mostrado no solo efectos en la mejoría de los síntomas, como el dolor y la funcionalidad [138,139], sino que también ha habido efectos en la conciencia corporal del paciente y la propiocepción asociada con la respiración y descompresión articular [147,154,155]. Los pocos estudios que han examinado el efecto de la RPG en el dolor de cuello crónico inespecífico han mostrado resultados positivos para aliviar el dolor, disminuir y aumentar la flexibilidad y la movilidad del cuello [152,154,156]. No obstante, los estudios sobre RPG deben interpretarse con cautela debido a la heterogeneidad de los resultados y la baja calidad de los ensayos clínicos [138,139].…”
Section: Reeducación Postural Globalunclassified